Local Wisdom: The Values System of Minangkabau Ethnic Customs as a Fundamental Basic of Educational Character in Indonesia - Taher, Najibah (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2018)
The function of National Education system has to build and develope the human character and personality in civilization of Indonesian based on the potentiality of the nature of Indonesian people. Indonesian people must behave in the good personality as a nation amongthe people in the world. Each citizent of The Republic of Indonesia must behave in a good personality: they have must be religious, deligent, clever, dicipline, brave, have a point of view, broad minded, dicipline, can develop mind set, good attitude, have adversity, plesant, human dignity, appreciate, honestly, human dignity and other vitues. One of the aspects influence of shaping human character is the values system of our commuty. In west Sumatera (Ethnicof Minangkabau} has specially values which is different of ohther community dealing with shapping character or personalty. Education system must be responsibility to educate people in shapping agood charater as a fundamental of educational system. In this occasion I would like to discussion in dealing with the basic aspect of implementing of educational character in our system must bebased on the value systemof the coomunity or society.Key word: Local Wisdom, Knowing Value System, Custom of Minangkabau, Fundamental Basic of Education, Character.